A Systemic Prime–Intrarectal Pull Strategy Raises Rectum-Resident CD8+ T Cells for Effective Protection in a Murine Model of LM-OVA Infection - He, Qian; Jiang, Lang; Cao, Kangli; Zhang, Linxia; Xie, Xinci; Zhang, Shuye; Ding, Xiangqing; He, Yongquan; Zhang, Miaomiao; Qiu, Tianyi; Jin, Xuanxuan; Zhao, Chen; et al. (Frontiers in Immunology, 2020)
As the entry sites of many pathogens such as human immunodeficiency virus (HIV), mucosal sites are defended by rapidly-reacting resident memory T cells (TRM). TRMs represent a special subpopulation of memory T cells that persist long-term in non-lymphoid sites without entering the circulation, provide the “sensing and alarming” role in first-line defense against infection. Rectum and vagina are the two primary mucosal portals for HIV entry. However, compared to vaginal TRM, rectal TRM is poorly understood. Herein, we investigated the optimal vaccination strategy to induce rectal TRM. We identified an intranasal prime-intrarectal boost (pull) strategy effective in engaging rectal TRM alongside circulating memory T cells, and demonstrated its protective efficacy in mice against infection of Listeria monocyogenes. On the contrary, the same vaccine delivered via either intranasal or intrarectal route failed to raise rectal TRM, setting it apart from vaginal TRM, which can be induced by both intranasal and intrarectal immunizations. Moreover, intramuscular prime was also effective in inducing retal TRM in combination with intrarectal pull, highlighting the need of a primed systemic T cell response. A comparison of different pull modalities led to the identification that raising rectal TRM is mainly driven by local antigen presence. We further demonstrated the interval between prime-boost steps to be critical for the induction of rectal TRM, revealing circulating recently activated CD8+ T cells as the likely primary pullable precursor of rectal TRM. Altogether, our studies lay a new framework for harnessing rectal TRM in vaccine development.